PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SEKOLAH DASAR - Cahyo Ningsih, Dewi; Sofia, Ari; Hariyanto; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning outcomes in Natural and Social Sciences (IPAS) among fifth-grade elementary school students served as the background for this study. This study aimed to determine the effect of using audio-visual learning media on students' IPAS learning outcomes. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The sample consisted of 37 students, including 19 students in the experimental group and 18 students in the control group. Data were collected through pretests and posttests and analyzed using the N-Gain test and the independent samples t-test. The results showed that the use of audio-visual learning media improved students' IPAS learning outcomes. The experimental group achieved higher posttest scores and an N-Gain score (0.60) than the control group (0.31). Furthermore, the independent samples t-test yielded a significance value of 0.010 (p < 0.05), indicating that the use of audio-visual learning media had a significant effect on IPAS learning outcomes among fifth-grade students at SD Negeri 1 Rulung Sari.